2021
DOI: 10.2196/24555
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Physician-Pharmacist Participation in the Management of Ambulatory Cancer Pain Through a Digital Health Platform: Randomized Controlled Trial

Abstract: Background Self-management of ambulatory cancer pain is full of challenges. Motivated by the need for better pain management, we developed a WeChat-supported platform, Medication Housekeeper (MediHK), to enhance communication, optimize outcomes, and promote self-management in the home setting. Objective We conducted a randomized controlled trial to assess whether the joint physician-pharmacist team through MediHK would provide better self-management of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“… 10 , 21 , 44 Collaboration between the joint team of doctors, nurses, and pharmacists has strengthened the communication and collaboration between medical personnel and patients, and improved the management of cancer pain symptoms. 21 , 32 , 33 Similar to these research results, our study found that, compared with conventional medical services, telemedicine intervention is beneficial in improving the pain intensity and pain interference of patients with cancer. Although the difference between the two groups was statistically significant, the clinical effect of this improvement was not very remarkable and was not considered to be clinically relevant.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 10 , 21 , 44 Collaboration between the joint team of doctors, nurses, and pharmacists has strengthened the communication and collaboration between medical personnel and patients, and improved the management of cancer pain symptoms. 21 , 32 , 33 Similar to these research results, our study found that, compared with conventional medical services, telemedicine intervention is beneficial in improving the pain intensity and pain interference of patients with cancer. Although the difference between the two groups was statistically significant, the clinical effect of this improvement was not very remarkable and was not considered to be clinically relevant.…”
Section: Discussionsupporting
confidence: 84%
“…After reading the full texts, 21 studies were included in the final analysis. 18 , 19 , 21 , 23 40 See Figure 1 for the flowchart of the detailed screening process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if the original records are incomplete, the completeness score of the report will be low. Some studies have reported that consultation with pharmacists' results in minimized ADR outcomes and more appropriate use of concomitant drugs compared with physician prescriptions alone 30 . Physicians may be better informed about medical history and biological data, whereas patients may be better informed of their medical history and other aetiologies compared with pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature suggests the important potential involvement of pharmacists as multidisciplinary team (MDT) members in managing cancer pain in terms of improving HRQoL, reducing medication non-compliance, and adverse drug reactions (ADRs) [ 9 11 ]. In preparation for this trial, the investigators of this study conducted a systematic review and meta-analysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%